2017
DOI: 10.1177/2325967116686774
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Maltracking Persists in Adolescent Females With Patellofemoral Pain

Abstract: Background:Patellofemoral pain is one of the most common conditions seen in sports medicine practices, particularly among adolescent females. However, the natural history of the underlying pathology in patellofemoral pain during puberty remains poorly understood.Purpose:The purpose of this longitudinal study is to assess changes in patellar maltracking patterns in subjects with patellofemoral pain as they mature from mid- to late adolescence.Study Design:Cohort study; Level of evidence, 3.Methods:Three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Indeed, a recent re-analysis of Sandow and Goodfellow’s data does not seem to support their own conclusions, with Luhann et al [ 100 ] highlighting that of the original 54 adolescents, 94% still had pain at final follow-up, with 54% reporting same or worse severity of symptoms. This pattern of poor long term prognosis continues in the adult populations, with a large proportion (> 50%) of people still reporting pain and dysfunction five to eight years after a six weeks evidenced based treatment programme [ 101 ]; yet the impression that PFP is a benign and self-limiting condition, with non-intervention advised, has continued to guide funders and stakeholders decision making for decades [ 102 ]. In the context of the high incidence and prevalence numbers, poor long term prognosis and high disability levels, PFP should be an urgent research priority.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent re-analysis of Sandow and Goodfellow’s data does not seem to support their own conclusions, with Luhann et al [ 100 ] highlighting that of the original 54 adolescents, 94% still had pain at final follow-up, with 54% reporting same or worse severity of symptoms. This pattern of poor long term prognosis continues in the adult populations, with a large proportion (> 50%) of people still reporting pain and dysfunction five to eight years after a six weeks evidenced based treatment programme [ 101 ]; yet the impression that PFP is a benign and self-limiting condition, with non-intervention advised, has continued to guide funders and stakeholders decision making for decades [ 102 ]. In the context of the high incidence and prevalence numbers, poor long term prognosis and high disability levels, PFP should be an urgent research priority.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have used dynamic MRI protocols, to investigate the correlation between patellofemoral morphology and kinematics, as well as the difference to healthy controls. Carlson et al investigated in the patellofemoral morphology and patellar tracking of female adolescent patients, who showed symptoms of patellofemoral pain 40,44 . However, these measuring techniques did not allow quantification of patellar tracking and the reliability was not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have provided measurements during unrealistic conditions, such as PFP evaluation in the supine position only [34] or while leaning on the equipment during the loading task [23]. For example, in a study by Esfandiarpour et al [19], the lunge test was performed with one leg supported on the ground, while the knee of the other leg was flexed at 90˚.…”
Section: Plos Onementioning
confidence: 99%
“…Carlson et al showed that a strongly contracted quadriceps reduce the bony constraint on the patella, causing the patella to deviate from normal tracking along the femoral groove [34]. Especially, in weight-bearing conditions, an activation imbalance of quadriceps causes the abnormal action of the patella in the PFP group [19].…”
Section: Plos Onementioning
confidence: 99%